Bilateral Recurrent Massive Earlobe Keloids : A Case Report And Review Of The Literature - Ninan Shiby; Gupta Ashish Kumar (Wolters Kluwer Medknow Publications, 2002)
Earlobe keloid secondary to ear piercing is a recognized complication and may be unsightly and often cause significant distress to the patient. The size of the keloid may very considerably; although usually small, large lesions weighing up to 38 g have been reported. This article describes a case of bilateral recurrent massive keloid of earlobes and review of literature.